Efficacy of E2-sub-unit marker and C-strain vaccines in reducing horizontal transmission of classical swine fever virus in weaner pigs. - Dewulf, J; Laevens, H; F. Koenen; Mintiens, K; de Kruif, A (Prev Vet Med, 2004)
At present, two types of vaccines against classical swine fever (CSF) virus are commercially available: E2 sub-unit marker vaccines and the conventional attenuated live C-strain vaccines. To evaluate the reduction of the horizontal virus transmission, three comparable experiments were carried out in which groups of weaner pigs (vaccinated with a marker vaccine or a C-strain vaccine) were challenged with CSF virus at 0, 7, and 14 days post-vaccination (dpv). Virus transmission was prevented totally when the challenge occurred at 14 dpv with an E2-marker vaccine (0/12 contact pigs positive in virus isolation (VI); R = 0 (0; 1.5)). At 7 dpv, transmission was reduced slightly (5/12 contact pigs positive in VI; R = 1.0 (0.3; 3.0)), whereas at 0dpv, vaccination had no effect on transmission (10/12 contact pigs positive in VI; R = 2.9 (1.5; 10.8)). In the C-strain-vaccinated pigs, no virus transmission was detected even when the challenge was performed at the same day as the vaccination (0/12 contact pigs positive in VI; R = 0 (0; 1.5)).
Keywords: Animals; Antibodies, Viral; Classical Swine Fever; Classical swine fever virus; Enzyme-Linked Immunosorbent Assay; Female; Genetic Markers; Leukocytes; Male; Swine; Vaccination; Vaccines, Marker; Viral Envelope Proteins; Viral Vaccines; Weaning